1997
DOI: 10.1037/0882-7974.12.2.263
|View full text |Cite
|
Sign up to set email alerts
|

Patterns of coping preferences for male and female caregivers of frail older adults.

Abstract: The similarities and differences in male and female caregivers' preferred strategies for coping and the perceived helpfulness of these strategies in managing caregiving stressors were examined in this study. Respondents were 170 caregivers (139 women and 31 men) who were primary caregivers for an elderly adult relative who was either cognitively impaired or physically frail. Results provide preliminary evidence that gender is related to frequency of use but not to the perceived helpfulness of specific coping s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
16
0

Year Published

2002
2002
2020
2020

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 41 publications
(16 citation statements)
references
References 23 publications
0
16
0
Order By: Relevance
“…It is uncertain whether the latter fact reflects a real gender difference in the severity of morbidity, burden, and strain as suggested by previous research 51 52 or a sex difference in coping and help seeking behaviour between male and female carers. 53 Future studies will need to ensure inclusion of a more representative sample of caregivers to fully test the generalisability of the treatment.…”
Section: Discussionmentioning
confidence: 99%
“…It is uncertain whether the latter fact reflects a real gender difference in the severity of morbidity, burden, and strain as suggested by previous research 51 52 or a sex difference in coping and help seeking behaviour between male and female carers. 53 Future studies will need to ensure inclusion of a more representative sample of caregivers to fully test the generalisability of the treatment.…”
Section: Discussionmentioning
confidence: 99%
“…Acceptance also acknowledges tolerance to criticism, misunderstandings, and outpourings of pain and frustration. DeVaries, Hamilton, Lovett, and Gallagher-Thompson (1998) showed that gender is not related to perceived helpfulness of specific coping strategies.…”
Section: Feelings and Attitudes Expressed By Caregiversmentioning
confidence: 97%
“…Traditionally, women have been socialized to be relationship oriented, whereas men have been socialized be task oriented. As a result, female caregivers are more likely than male ones to pray for guidance, talk with a friend, and get busy with other activities to keep their minds off the problem (De Vries, Hamilton, Lovett, & Gallagher-Thompson, 1997; Lutzky & Knight, 1994). Findings from prior research regarding race and ethnicity have been mixed, however.…”
Section: Factors Associated With Copingmentioning
confidence: 99%